An Auto-fluorescence Guided Surgical Approach Performed with Er:YAG Laser and Nd:YAG Low Level Laser Therapy for Medication-related Osteonecrosis of the Jaw - Giovannacci,, Ilaria; Meleti, Marco; Bonanini, Mauro; Vescovi, Paolo (UI Scholars Hub, 2015)
Medication-Related Osteonecrosis of the Jaw (MRONJ) therapy remains an unresolved problem. The proposed conservative and surgical treatment regimens are associated to contradictory success rates. Surgical approach with Er:YAG laser is associated to significant better results compared to medical treatment and traditional surgical approaches. Objective: To describe a new surgical approach that couples the advantages of the Er:YAG laser and the usefulness of the AF in highlighting surgical margins. One of the difficulties encountered during surgical removal of a MRONJ is the precise individuation of necrotic bone margins. Case Report: A case of Stage III mandibular osteonecrosis treated with a new surgical approach is presented. The aim is to describe an auto-fluorescence (AF) guided surgical approach performed with Er:YAG laser and Nd:YAG Low Level Laser Therapy (LLLT). After one month of follow-up, the complete mucosal healing was evident and symptoms was unobserved. Such a technique allowed a highly accurate and minimally invasive approach through the selective ablation of the non-/hypofluorescent areas. Conclusion: Taking into account the advantages of laser therapy and the possible effectiveness of the AF in highlighting surgical margins, this approach would probably achieve excellent outcomes.